The impact of television programmes on Muslim women dressing: social learning theory - Wok, Saodah (IIUM Press, 2009)
Ever since television takes its strike, it has remained the most influential medium among the mass media. It can be considered a credible source of information. The reasons being the full colour, action packed, real actors films make TV seem to be real to the audience. The influence of TV on teenagers, adolescents and youth is widespread. The influence is mainly on their dressing and attire, that is, what they wear and what they use to adorn themselves. It is hoped that Muslim teenagers, adolescents and youths are less likely to be influenced by the fashion trends through TV compared to their counterparts from other religions. Therefore, it is the intent of this study to find out the influence of TV on Muslim women across all ages.